2021
DOI: 10.3390/genealogy5020032
|View full text |Cite
|
Sign up to set email alerts
|

The Historical Trauma and Resilience of Individuals of Mexican Ancestry in the United States: A Scoping Literature Review and Emerging Conceptual Framework

Abstract: Recently, Black, Indigenous, and other People of Color (BIPOC) have encountered an escalation in adverse social conditions and trauma events in the United States. For individuals of Mexican ancestry in the United States (IMA-US), these recent events represent the latest chapter in their history of adversity: a history that can help us understand their social and health disparities. This paper utilized a scoping review to provide a historical and interdisciplinary perspective on discussions of mental health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 138 publications
(530 reference statements)
1
11
0
Order By: Relevance
“…The adapted stress and coping framework (Figure 1; Walters et al, 2002) and intersectionality (Bowleg, 2021; Crenshaw, 1991; Hill Collins, 2019; Poteat, 2021) theoretically situate our results, by contextualizing ethnic discrimination and acculturative stress as “stress” (Cano et al, 2014; Cano, Schwartz, et al, 2021; Cheng, 2022; Cheng et al, 2020) and familism support and ethnic identity as “coping” or protective factors (Krieger, 2011; Krieger et al, 2010), within historical foundations of the social determinants of health (Cerdeña et al, 2021; Orozco-Figueroa, 2021). Settler colonialism’s production (e.g., Indigenous genocide, African enslavement; Cerdeña et al, 2021; Orozco-Figueroa, 2021) and legacy of racialization (Canizales & Agius Vallejo, 2021), political violence, and migration-related multigenerational stressors, drive social, health, and economic inequities across Latin America and the United States. Intergenerational traumas (Cerdeña et al, 2021; Chavez-Dueñas et al, 2019)—or psychological harms resulting from historically oppressive systems and events that impact the health and well-being of subsequent generations (Cerdeña et al, 2021; Chavez-Dueñas et al, 2019; Estrada, 2009; Orozco-Figueroa, 2021)—can result.…”
Section: Discussionsupporting
confidence: 61%
“…The adapted stress and coping framework (Figure 1; Walters et al, 2002) and intersectionality (Bowleg, 2021; Crenshaw, 1991; Hill Collins, 2019; Poteat, 2021) theoretically situate our results, by contextualizing ethnic discrimination and acculturative stress as “stress” (Cano et al, 2014; Cano, Schwartz, et al, 2021; Cheng, 2022; Cheng et al, 2020) and familism support and ethnic identity as “coping” or protective factors (Krieger, 2011; Krieger et al, 2010), within historical foundations of the social determinants of health (Cerdeña et al, 2021; Orozco-Figueroa, 2021). Settler colonialism’s production (e.g., Indigenous genocide, African enslavement; Cerdeña et al, 2021; Orozco-Figueroa, 2021) and legacy of racialization (Canizales & Agius Vallejo, 2021), political violence, and migration-related multigenerational stressors, drive social, health, and economic inequities across Latin America and the United States. Intergenerational traumas (Cerdeña et al, 2021; Chavez-Dueñas et al, 2019)—or psychological harms resulting from historically oppressive systems and events that impact the health and well-being of subsequent generations (Cerdeña et al, 2021; Chavez-Dueñas et al, 2019; Estrada, 2009; Orozco-Figueroa, 2021)—can result.…”
Section: Discussionsupporting
confidence: 61%
“…In order to apply these findings more broadly, the next step in this research should be to implement these adapted measures with a larger and more heterogeneous sample of Latinx/@ immigrant respondents and use mixed methods to understand the complex reality of Latinx/@ immigrants whose experiences are currently being shaped by the social–cultural–political climate of the United States and whose experiences have been shaped for generations by structural violence, colonialization, and discrimination in Latin America and in the United States. Limiting this research to individual-level quantitative data may miss important aspects of how discrimination and loss, across the lifecourse and over generations, impacts health of Latinx/@ populations, particularly for immigrant populations (Cerdeña et al, 2021; Orozco-Figueroa, 2021). Combining quantitative methods with qualitative methods is ideal to address the complexities of the migration experience, at multiple levels, and across generations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review examining intergenerational trauma among Latinx/@ populations in the United States and Canada found that the primary focus of the published literature is on individual-level experiences, with a strong focus on the mother–child dyad, with limited focus on the “contextualized trauma within frameworks of structural violence, or the political and economic organization of the social world that put individuals and populations in harm’s way” (Cerdeña et al, 2021). Furthermore, a recent review by Orozco-Figueroa provides a historical and interdisciplinary perspective on mental health disorders drawing on a more Indigenous-based conceptualization for individuals of Mexican ancestry in the United States and highlighting the impact of historically traumatic events as well as intergenerational responses to historical trauma (Orozco-Figueroa, 2021). Finally, Cacari-Stone et al demonstrate that historical trauma, specifically the legacy of colonialism and structural racism and oppression, for mestizo Latinx/@ communities is an important driver of health and well-being (Cacari Stone et al, 2021).…”
mentioning
confidence: 99%
“…Multiple generations of Mexican Americans have experienced anti-Mexican sentiment through prejudice, discrimination and institutional violence [1,2]. Interrupting this cycle of psychosocial stress among Mexican American adolescents may be the first step in fostering cultural resiliency and reducing the negative effects of acculturative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Negative perceptions, opinions and discriminatory practices toward immigrant and non-immigrant Latinos have long been part of the socio-historical reality in the American Southwest [1]. Historical documents and research findings convincingly demonstrate the insidious nature of discrimination and prejudice experienced by Mexican Americans over the past 170 years [2,3].…”
Section: Introductionmentioning
confidence: 93%